Health facility and workforce factors influencing utilization of reproductive health services in selected South Sudan public health facilities - Onak, Emmanuel Timothy Thwol; Odongo, Alfred Owino; Kariuki, John (International Journal Of Community Medicine And Public Health, 2024)
Background: Despite representing only one-tenth of the global population and 20% of worldwide births, nearly half of all maternal deaths occur in Africa. RH issues account for up to 18% of the global disease burden and 32% for women of reproductive age. Access to essential RH interventions, including family planning, is limited in Sub-Saharan Africa, characterized by low contraceptive use (13%) and a high total fertility rate (5.5 children per woman). Methods: This study used a mixed-method research design, integrating both quantitative and qualitative approaches to provide a comprehensive understanding of the factors influencing RH service utilization in South Sudan. This design allowed for in-depth exploration and quantitative analysis of data patterns and trends. Results: The study identified significant barriers to RHS utilization among women in South Sudan. Although many women were aware of the nearest RH clinic, 42.3% were not. Accessibility was a major issue, with 45.8% of women living more than 2 km from the nearest clinic, and the average distance being 2.2 km. Statistically significant relationships were found between health facility characteristics and RHS use. Interviews indicated that higher education levels among healthcare providers improved their skills, critical thinking, and ability to deliver comprehensive RH care, positively influencing service utilization. Conclusions: Key determinants of RHS utilization included awareness of services, proximity to facilities, and availability of contraceptives. The health workforce’s education, staffing levels, workload management, and fair compensation were also critical. To improve RHS utilization, the study recommends community outreach to raise awareness, expand facilities in remote areas, and offer diverse contraceptive options. Future research should address limitations like sampling biases and regional focus, explore broader geographical areas, longitudinal trends, and the impact of specific interventions, and consider technology’s role in enhancing access.